Applying Songs as a Teaching Strategy to Teach Vocabulary at the Tenth Grade of SMA Negeri 13 MBD - Magelang, Mira; Lekatompessy, Jeny; Anaktototy, Karolis (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2023)
This study focused on teaching students’ vocabulary through song as the teaching method. It aimed to find out whether there are any differences on students’ vocabulary achievement after being taught by using appropriate and can be used or not. This study was conducted in a tenth-grade class at SMA Negeri 13 MBD. The data was collected from the result of students‟ test in cycle 1 to cycle 2 and the result of questionnaire. The result of this study showed that song as teaching method was successfully implemented to increase and to enrich students‟ vocabulary that can be seen on students‟ score in students‟ result of cycle 2, 75% students were able to reach the indicator of success with the range scores from 71-100. The result in questionnaire also showed that students had positive responses toward the implementation of song method. Song as the teaching method was effective to motivate and engage students to learn and memorize the vocabulary during the learning process and it was appropriate for assisting students to learn vocabulary from home and also can help students to create their own sentence.